The Influence of Ultrasound on Formation of Self-organized Uniform Nanoclusters - R.M. Peleshchak; O.V. Kuzyk; O.O. Dan’kiv (Журнал нано- та електронної фізики)
The non-linear diffusion-deformation theory of self-organization of nanoclusters of dot defects in semiconductor exposed to ultrasound treatment that considers the interaction of defects among themselves and with atoms of a matrix via the elastic field created by dot defects and an acoustic wave is developed. Within this theory the influence of ultrasound on the conditions of formation of spherical nanoclusters and their radius is investigated. The nanocluster size depending on average concentration of defects and amplitude of an acoustic wave is determined. It is established that ultrasonic treatment of the semiconductor in the process of formation of an ensemble of nanoclusters leads to reduction of dispersion of their sizes.